Time-dependent simulation of the flow reduction of D2 and T2 in the KATRIN experiment. (January 2019) - Friedel, F.; Röttele, C.; Schimpf, L.; Wolf, J.; Drexlin, G.; Hackenjos, M.; Jansen, A.; Steidl, M.; Valerius, K.
Abstract: The KArlsruhe TRItium Neutrino experiment (KATRIN) aims to measure the effective electron anti-neutrino mass with an unprecedented sensitivity of 0.2 eV/c 2, using β -electrons from tritium decay. Superconducting magnets will guide the electrons through a vacuum beamline from the windowless gaseous tritium source through differential and cryogenic pumping sections to a high resolution spectrometer. At the same time tritium gas has to be prevented from entering the spectrometer. Therefore, the pumping sections have to reduce the tritium flow by at least 14 orders of magnitude. This paper describes various simulation methods in the molecular flow regime used to determine the expected gas flow reduction in the pumping sections for deuterium (commissioning runs) and for radioactive tritium. Simulations with MolFlow+ and with an analytical model are compared with each other, and with the stringent requirements of the KATRIN experiment. Highlights: Simulation of the gas flow of D2 and T2 in differential and the cryogenic pumping in the KATRIN experiment. The total gas flow is reduced by more than 14 orders of magnitude with the combined pumping systems. Tritium migration along the beam line due to the sojourn time on Ar-frost and β-induced desorption are investigated. Two simulation methods are compared; TPMC simulation with MolFlow+, and a custom-made C++ code.